Chirped solitary waves of the perturbed Chen-Lee-Liu equation and modulation instability in optical monomode fibres - Houwe, Alphonse; Abbagari, Souleymanou; Almohsen, Bandar; Betchewe, Gambo; İnç, Mustafa; Doka, Serge Y. (Springer, 2021)
In this paper, we show out the chirped and the corresponding chirp with their stability to the perturbed Chen-Lee-Liu equation with self-phase modulation and nonlinear dispersions. By employing the traveling-wave technique, we establish directly the nonlinear ordinary differential (NODE) equation. Based on the parameters of the obtained NODE, several cases of the exact traveling wave have been obtained with their corresponding chirp. We, also note that the group velocity dispersion, the self-phase modulation and the nonlinear dispersion terms have impacted the gain spectrum of the modulation instability (MI). The one important aspect is that without computer codes all these results were obtained. These results will be certainly helpful in optical fibers.
Keywords: Chirped optical solitons; Perturbed Chen-Lee-Liu equation; Modulation Instability